Knowledge, Attitude, And Practices Of Non-Communicable Diseases: Comparison Between Orang Asli And Malay From Rural Area In Negeri Sembilan, Malaysia: A Comparative Study - Ithnin M.; Juliana N.; Effendy N.M.; Mohd Rani M.D.; Nadeeya'ayn Umaisara Mohamad Nor (Universiti Sains Islam Malaysia, 2024)
Indexed by SCOPUS/MYCITE